Ultrasonic measurement of oil film thickness in a four-layer structure for applications including sliding bearings with a thin coating. (October 2022) - Dou, Pan; Zheng, Peng; Jia, Yaping; Wu, Tonghai; Yu, Min; Reddyhoff, Tom; Liao, Wei-Hsin; Peng, Zhongxiao
Abstract: Owing to the non-destructive feature, ultrasonic techniques have been developed to measure the oil film thickness in sliding bearings. If a bearing has a thick coating, then the ultrasonic reflection from a four-layer structure consisting of pad-coating-oil-steel is equivalent to that of coating-oil-steel, where classical three-layered ultrasonic models can be applicable to estimate the thickness of oil film. However, in the case of thinly coated bearings, the measurement accuracy of existing models deteriorates due to signal overlapping. Despite two signal processing methods that have been attempted to isolate the desirable oil film echoes, the challenge remains when dealing with widely ranged oil film thickness. In contrast, this paper presents a unified ultrasonic model that enables accurate measurements of oil film thickness that is widely ranged in a thinly coated bearing. This model is mathematically derived from multi-layer continuum models with the oil thickness and the complex reflection coefficients correlated. It also takes into account two typical locations of the embedded transducer in the bearing. The viability of the proposed method is experimentally validated using a high-precision calibration rig, showing that the oil film that ranges from 6 μm to 97 μm can be accurately measured in the application to thinly coated (around 400 μm) bearings, where the measurement errors are not greater than 7.4%.